Evaluating Differentiated Chemistry Instruction in Senior High Schools Using Stake’s Countenance Model: A Study in Gorontalo City - Suryanto, Suryanto; Lukum, Astin; La Kilo, Akram; Laliyo, Lukman A.R.; Pikoli, Masrid; Salimi, Yuszda K. (Universitas Negeri Gorontalo, 2025)
This study aims to evaluate the implementation of differentiated instruction in Chemistry subject for Grade 10 students across senior high schools in Gorontalo City using Stake’s Countenance Model. The evaluation focused on three key components: antecedent (lesson planning), transaction (instructional implementation), and outcome (student learning results). Data were collected through the analysis of lesson plans and teaching modules, classroom observations, teacher interviews, and assessments of student learning outcomes. The analysis employed both congruence and contingency approaches. The findings indicate that both lesson planning and instructional implementation fall into the